Internal Audit Model for Strengthening Governance in Halal Certification Assistance Institutions - Dedi Amrizal; Yusriati; Danisha Salsabilla Hasibuan (LifeSciFi, 2025)
Mentoring plays a crucial role in the success of community empowerment programs, especially in the context of halal product certification for MSMEs. Prior to submitting documents to the Fatwa Commission, the Halal Product Process Mentoring Institution (LP3H) is responsible for conducting an internal audit to ensure procedural compliance, strengthen consumer trust, and support the growth of the halal market. This study aims to develop and implement an effective internal audit model for LP3H in North Sumatra as part of good governance practices. Employing a Research and Development (R&D) approach based on Borg and Gall's ten-step model—grouped into five stages for field efficiency—this study has completed 50% of its implementation. The stages include initial research, model design, model development, implementation, and evaluation. Results indicate that the developed internal audit model significantly improves LP3H's ability to supervise and evaluate halal mentoring activities, reducing errors and ensuring accountability. The model has been tested using the N-Gain method and shown to be effective. It provides a reliable tool to support LP3H in maintaining mentoring quality and certifying halal products for MSMEs. Future research is recommended to assess its adaptability across various LP3H institutions in other regions.